Sequencing-based transcriptome analysis reveals diversification of immune response- and angiogenesis-related expression patterns of early-stage cervical carcinoma as compared with high-grade CIN - Kurmyshkina, Olga V.; Dobrynin, Pavel V.; Kovchur, Pavel I.; Volkova, Tatyana O. (Frontiers in Immunology, 2023)
Background Molecular diversity of virus-associated cervical cancer remains a relatively underexplored issue, and interrelations of immunologic and angiogenic features during the establishment of a particular landscape of the cervical cancer microenvironment are not well-characterized, especially for its earliest clinical stages, although this may provide insight into the mechanisms behind the differences in tumor aggressiveness, treatment responsiveness and prognosis. In this research, we were aimed at identifying transcriptomic landscapes of early-stage cervical carcinoma that differ substantially in their immune-related characteristics, patterns of signaling pathways and composition of the microenvironment in comparison with immediate precursor (intraepithelial) lesions. Methods We performed the Illumina platform-based RNA sequencing using a panel of fresh tissue samples that included human papillomavirus-positive cervical intraepithelial neoplastic lesions (CIN), invasive squamous carcinoma of the cervix of FIGO IA1-IIB stages, and morphologically normal epithelium. The derived transcriptomic profiles were bioinformatically analyzed and compared by patterns of signaling pathway activation, distribution of tumor-infiltrating cell populations, and genomic regions involved. Result According to hierarchical cluster analysis of the whole-transcriptome profiles, tissue samples were distributed between three groups, or gene expression patterns (the one comprising most pre-cancer cases and the other two encompassing mostly early-stage invasive cancer cases). Differentially expressed genes were retrieved in each intergroup pairwise comparison followed by Gene Ontology analysis. Gene set enrichment analysis of the two groups of tumor samples in comparison with the CIN group identified substantial differences in immunological and angiogenic properties between tumorous groups suggesting the development of different molecular phenotypes. Cell composition analysis confirmed the diverse changes in the abundancies of immune and non-immune populations and, accordingly, different impacts of the immune and stromal compartments on the tumor microenvironment in these two groups of tumors compared to CIN. Positional gene expression analysis demonstrated that the identified transcriptomic differences were linked to different chromosomal regions and co-localized with particular gene families implicated in immune regulation, inflammation, cell differentiation, and tumor invasion. Conclusions Overall, detection of different transcriptomic patterns of invasive cervical carcinoma at its earliest stages supports the diverse impacts of immune response- and angiogenesis-related mechanisms on the onset of tumor invasion and progression. This may provide new options for broadening the applicability and increasing the efficiency of target anti-angiogenic and immune-based therapy of virus-associated cervical carcinoma.